Leadership education program in higher education according to Dr. (H.C) K.H. Abdullah Syukri Zakasyi, Lc., M.A. - Nesa Novrizal; Wido Supraha; Nirwan Syafrin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Leadership education is an important element in shaping the character and competence of qualified college graduates. This research aims to develop a leadership education program in higher education based on the views of Dr. (H.C.) KH. Abdullah Syukri Zarkasyi, Lc., M.A. The method used in this research is Research and Development (R&D) with the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. At the analysis stage, a needs analysis was conducted through a questionnaire with a Guttman scale to lecturers and students of universities in Indonesia and abroad. This leadership education program includes various activities such as Cultivation Islamic Worldview, tadabbur tafsir hadith leadership, Contemporary Fiqh Learning, Conflict Management and Problem-solving Training, public speaking training, and community service programs. The feasibility test results validated by three experts show that this program is effective in producing leaders from among students and is relevant to the current needs of higher education.